2011
DOI: 10.1179/2045772311y.0000000018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of training methods to improve walking in persons with chronic spinal cord injury: a randomized clinical trial

Abstract: Objective: To compare two forms of device-specific training -body-weight-supported (BWS) ambulation on a fixed track (TRK) and BWS ambulation on a treadmill (TM) -to comprehensive physical therapy (PT) for improving walking speed in persons with chronic, motor-incomplete spinal cord injury (SCI). Methods: Thirty-five adult subjects with a history of chronic SCI (>1 year; AIS 'C' or 'D') participated in a 13-week (1 hour/day; 3 days per week) training program. Subjects were randomized into one of the three trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 66 publications
12
121
0
Order By: Relevance
“…2 Walking speed can be improved in those with chronic iSCI with activity-based therapies. 45 Walking ability and psychological well-being improved in 35 adults with chronic iSCI for more than 1 year (AIS C and AIS D), both with BWSTT and walking in a fixed track device with body-weight support. Improved walking speed was associated with increased balance and muscle strength.…”
Section: Recovery Of Walking Through Activity-based Therapiesmentioning
confidence: 99%
“…2 Walking speed can be improved in those with chronic iSCI with activity-based therapies. 45 Walking ability and psychological well-being improved in 35 adults with chronic iSCI for more than 1 year (AIS C and AIS D), both with BWSTT and walking in a fixed track device with body-weight support. Improved walking speed was associated with increased balance and muscle strength.…”
Section: Recovery Of Walking Through Activity-based Therapiesmentioning
confidence: 99%
“…Many of the most common conditions identified, such as cardiovascular disease, diabetes, BMD loss, fatigue, obstructive sleep apnea appear to be related to a sedentary lifestyle, obesity or both. Significant effort may be needed to develop and evaluate the efficacy of ways for individuals with SCI to (1) increase weight-bearing and both improve and maintain cardiovascular fitness 34 and (2) help individuals with SCI avoid gaining weight as they age. Treatments that successfully address these factors may prevent or ameliorate a large number of the secondary conditions that in our review were associated with increasing age.…”
Section: Findings Regarding Age and Duration Effectsmentioning
confidence: 99%
“…The median (IQR) number of CONSORT items per trial that was 'fully reported' was 11/37 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The median (IQR) number of CONSORT items per trial that was either 'fully reported' or 'not relevant' or 'not reported but unable to determine if relevant/done' was 20/37 items (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%